Factors that contribute to customer loyalty of Celcom post paid user in Kajang in 2008 / Hazwani Ahmad - Ahmad, Hazwani (Faculty Of Business and Management, 2008)
Celcom (Malaysia) Berhad is the oldest telecommunications company in Malaysia. Celcom is one of a member of TM group of companies. Being on of the very few companies in Malaysia to originally obtain a cellular phone license, it successfully introduced mobile telephony in Malaysia through its ART-900 service using first generation NMT-900 technology. It uses identifier of '013', '0148' and '019'.